Resistance of The Quraysh Infidels Against The Prophet Muhammad in The Makkah Period: A Thematic Study of Ibn Kathīr in Tafsīr al-Qur’ān al-‘Aẓīm - Bashori; Syamsuni; Muhammad Ilham Habibie (UIN Sunan Kalijaga Yogyakarta, 2025)
The resistance of the Disbelieving Quraysh to the da‘wah of the Prophet Muhammad saw. The Meccan period represents a crucial phase in the early history of Islam. This article aims to analyze the causes and forms of Quraysh resistance to the prophetic mission by examining Ibn Kathīr’s interpretation of relevant Qur’anic verses. This study employs a qualitative library research design using the thematic exegesis (tafsīr mawdhū‘ī) method as formulated by al-Farmāwī. The findings indicate that Quraysh opposition was not merely rooted in theological rejection of monotheism, but was also driven by strong fanaticism toward ancestral traditions, social arrogance of the Meccan elite, and concerns over the loss of economic and political dominance. The resistance manifested in a gradual and systematic manner, beginning with verbal propaganda and psychological pressure, followed by physical persecution of the weak, social and economic boycotts, and culminating in conspiracies to assassinate the Prophet Muhammad saw. Through Ibn Kathīr’s exegetical perspective, this study affirms that Quraysh resistance was structural and strategic in nature, aimed at preserving the established socio-political order in Mecca. Penolakan dan perlawanan kaum kafir Quraisy terhadap dakwah Nabi Muhammad saw. pada periode Makkah merupakan fenomena penting dalam sejarah awal Islam. Artikel ini bertujuan menganalisis sebab-sebab dan bentuk-bentuk perlawanan Quraisy terhadap misi kenabian dengan merujuk pada penafsiran Ibn Kathīr terhadap ayat-ayat Al-Qur’an yang relevan. Penelitian ini menggunakan pendekatan kualitatif berbasis studi kepustakaan dengan metode tafsir tematik (tafsir mawdhū‘ī) sebagaimana dirumuskan oleh al-Farmāwī. Hasil penelitian menunjukkan bahwa perlawanan Quraisy tidak semata-mata didorong oleh penolakan teologis terhadap ajaran tauhid, tetapi juga oleh fanatisme terhadap tradisi leluhur, arogansi sosial kaum elite, serta kekhawatiran akan hilangnya dominasi ekonomi dan politik di Makkah. Bentuk perlawanan tersebut termanifestasi secara bertahap, mulai dari propaganda verbal, tekanan psikologis, penyiksaan fisik terhadap kaum lemah, pemboikotan sosial-ekonomi, hingga konspirasi pembunuhan terhadap Nabi Muhammad saw. Melalui perspektif tafsir Ibn Kathīr, artikel ini menegaskan bahwa perlawanan Quraisy bersifat struktural dan sistematis sebagai upaya mempertahankan status quo kekuasaan.